Advancing Information Systems Theories, Volume II Products and Digitalisation - Willcocks, Leslie P.; Hassan, Nik R.; Rivard, Suzanne (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
Information systems research (IS) is an exciting multidisciplinary area that links the rapidly changing technology of information (or communications and information technology, ICT) to the business and social environment. Lately, the discourse surrounding information and systems has leaped into the consciousness of the public in unprecedented ways through the rise of social media, the Internet of Things (IoT), 'fake news' and the weaponization of information, to name a few. Unfortunately, it has been felt that these developments are overtaking the ability of the IS field to address them, in part, because the field itself lacks its own native theories. It is well known that the IS field undertakes its research using theories from its 'reference disciplines' such as management, social psychology, economics, communication and computer science, but what this book offers is a clarification and implementation of the discipline's own foundational theory. This book is the companion volume to Advancing Information Systems Theories: Volume I, and part of a three part series that aims to advance IS research. This volume addresses the products of information systems theories, examining design principles, information, practice principles for robotics, and other concepts integral to developing theory. The book will be of interest to academics studying information systems, Big Data, digital business, information technology, innovation management, and digital management. Leslie Willcocks is Emeritus Professor at London School of Economics and Political Science and is an Associate Fellow of Green Templeton College, University of Oxford, UK. Nik Rushdi Hassan is Professor of Management Information Systems (MIS) and Business Analytics at the Labovitz School of Business and Economics (LSBE), University of Minnesota Duluth, USA. Suzanne Rivard is a Professor of Information Technology at HEC Montreal and is the HEC Montreal Endowed Chair in Strategic Management of Information Technology.
1. Introduction: On Types of Products of Theorizing -- 2. Useful Products in Information Systems Theorizing: A Discursive Formation Perspective -- 3. Debating Genres And IS Research: The Case Of Action Principles For Service Automation -- 4. A Paradigm Shift in Understanding Digital Objects in IS: A Semiotic Perspective on Artificial Intelligence Technologies -- 5. A Cybernetic Theory of the Impact of Implementers' Actions on User Resistance to Information Technology Implementation -- 6. Interrogating Sociomateriality: An Integrative Semiotics Framework For Information Systems -- 7. When Crowds Play God: A Promethean Perspective on Crowdfunding -- 8. Routinization of Digital Transformation of Work: A Discursive Practice Orientation Towards a Native IS Theory -- 9. Patterns for Visualizing the Aesthetic Qualities of Business Processes -- 10. Information Theory in IS -- 11. The Primacy of Concepts and Implications for the IS Field -- 12. Propositions For a Future Information Exchange Theory to Support Decision Making -- 13. New Guidelines for Null Hypothesis Significance Testing in Hypothetico-Deductive IS Research.
Keywords: Technological innovations; Business information services; Innovation and Technology Management; IT in Business